PENGARUH MEDIA FLASHCARD TERHADAP HASIL BELAJAR SISWA PADA MATERI PLANTAE KELAS X MIA 2 MAS DARUL ULUM - Nabilah Muslimah; Laili Fitri Yeni; Titin Titin (Universitas Tanjungpura, 2020)
AbstractThis study aims to determine the effect of flashcard media on student learningoutcomes in Plantae class X MIA 2 MAS Darul Ulum. The population used in thisstudy was class X MIA 2 MAS Darul Ulum. The form of research is an experimentwith the design used in this study is Pre-experimental Design. The design used is a one-group pretest-posttest. Sampling using purposive sampling amounted to 14 students. Data collection tool is a test of a learning outcomes in the form of objective questions. The results showed that the average score of students learning outcomes after the use of flashcard media was 19,86 and before the use of them flashcard 11,14. Data analysis results using the t test with ? = 5% obtained t count > t table (13,41074>1,77093), meaning that there are significant differences between student learning outcomes before and after the use of the flashcard. It can be concluded that the flashcard learning media has an influence on student learning outcomes in Plantae material class X MIA 2 MAS Darul Ulum. Keyword: Flashcard, Learning Outcomes, Plantae